2017
DOI: 10.1021/acs.iecr.7b02818
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Crystallization of Sodium Chloride via Hollow Fiber Devices to Convert Waste Concentrated Brines to Useful Products

Abstract: Cooling crystallization via hollow fiber devices emerges as a new technology suitable for salt production from concentrated seawater brine. To generate high-quality NaCl crystals, a solid hollow fiber cooling crystallization (SHFCC) system was developed in this study using lab-made PVDF hollow fibers as the heat-exchanger and magnetic stirring as the downstream mixing device. Experiments were conducted to investigate the influences of downstream agitation methods and operation parameters on crystal properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…32−34 Owing to this advantage, researchers have reported that the membrane module serves as a novel heat exchanger for cooling operations, with fruitful achievements. 25,35 All of the above properties of the polymeric hollow fiber membrane can potentially benefit the cooling crystallization control via heterogeneous nucleation and high heat transfer efficiency, which have not been investigated in depth.…”
Section: Introductionmentioning
confidence: 99%
“…32−34 Owing to this advantage, researchers have reported that the membrane module serves as a novel heat exchanger for cooling operations, with fruitful achievements. 25,35 All of the above properties of the polymeric hollow fiber membrane can potentially benefit the cooling crystallization control via heterogeneous nucleation and high heat transfer efficiency, which have not been investigated in depth.…”
Section: Introductionmentioning
confidence: 99%
“…22 Luo et al successfully produced salt crystals from NaCl brine and concentrated synthetic seawater using the SHFCC system combined with ultrasonication or magnetic stirring. 23 Zarkadas and Sirkar also reported that antisolvent crystallization of drugs can be realized by using porous hollowfiber devices. 24 On this basis, Fern et al used indomethacin as a model drug to study the effect of mixing conditions of drug solution on crystal formation in a porous hollow-fiber membrane module.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the disadvantages of traditional methods, membrane-based technologies have been proposed to generate polymer-coated particles due to their excellent fiber properties: low weight, no metal contamination, and affordable price. , Zarkadas and Sirkar prepared paracetamol crystals using the SHFCC device and found that the average size of the crystals could be effectively controlled by changing the temperature of the coolant . Luo et al successfully produced salt crystals from NaCl brine and concentrated synthetic seawater using the SHFCC system combined with ultrasonication or magnetic stirring . Zarkadas and Sirkar also reported that antisolvent crystallization of drugs can be realized by using porous hollow-fiber devices .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, membrane crystallization (MCr), an innovative hybrid separation technology combining membrane technology with crystallization, has rapidly developed . With the intrinsic advantages of membrane technology and an improved energy utilization efficiency, MCr can simultaneously produce the desired crystal product and ultrapure solvent with relatively low energy input . The hollow fiber membrane module utilized in MCr provides a plentiful and uniform contact interface for the mass transfer of the crystallization solution, which facilitates the precise control of the supersaturation degree and micromixing condition.…”
Section: Introductionmentioning
confidence: 99%